The Interest of the Balinese People in the use of Electric Vehicles - Arif Devi Dwipayana; Adrian Pradana; I Putu Adi Suryasa; I Gusti Bagus Eka Nitiyasa (Jurnal Teknologi Transportasi dan Logistik, 2022)
Currently, the use of electric vehicles is experiencing very rapid development in several countries, partly due to the provision of subsidies by the government so that it can support environmentally friendly energy. Following up on Presidential Regulation 55 of 2019 the Governor of Bali Wayan Koster issued the Bali Governor Regulation Number 48 of 2019 concerning the Use of Battery-Based Electric Motorized Vehicles (KBL). The purpose of this study was to analyze the effect of income levels, electric vehicle taxes, product prices of electric vehicles, mileage of electric vehicles and the availability of SPKLU on public interest in using electric vehicles. The sample is 150 people who are in four sub-districts of Denpasar City and other areas of Bali. The data analysis technique used multiple linear regression formula analysis with the help of SPSS version 24 software. The results showed that the income level variable had a positive and significant effect on interest, the vehicle tax variable had a negative and insignificant effect on interest, the product price variable had a positive and significant effect on interest. the mileage variable has a positive and significant effect on interest and the SPKLU availability variable has a positive and significant effect on interest